Studies on New Guinean giant stick-insects of the tribe Stephanacridini Günther, 1953, with the descriptions of a new genus and three new species of Stephanacris Redtenbacher, 1908 (Phasmatodea: "Anareolatae") - Hennemann, Frank H.; Conle, Oskar V. (Zootaxa, 2006)
The genus Hermarchus STÅL, 1875 (type-species: Phibalosoma pythonius Westwood, 1859) is an artificial taxon. The new genus Macrophasma n. gen. (type-species: Hermarchus biroi Redtenbacher, 1908) is described to contain all New Guinean species currently in Hermarchus Stål, as these differ considerably from the type-species of Hermarchus Stål from Fiji by various features of the insects and eggs. Hermarchus biroi Redtenbacher, 1908, H. lyratus Redtenbacher, 1908 and H. oreitrephes Günther, 1929 are transferred to Macrophasma n. gen.. Hermarchus annulatus Günther, 1929 and H. muelleri Redtenbacher, 1908 are shown to be synonyms of H. biroi Redtenbacher, 1908 (n. syn.). A lectotype is designated for M. biroi (Redtenbacher, 1908) with the egg described and illustrated. Three new species of the genus Stephanacris Redtenbacher, 1908 from New Guinea are described and illustrated from the & & and eggs: Stephanacris draconius n. sp. from Papua New Guinea, Stephanacris multilobatus n. sp. from southeast West Papua and Stephanacris laeviceps n. sp. from northwest West Papua. Holotypes are deposited in ZSMC and RMNH, paratypes in the first and second author’s collections.